2019
DOI: 10.1111/ajo.13004
|View full text |Cite
|
Sign up to set email alerts
|

Use of intracytoplasmic sperm injection (ICSI) in normospermic men may result in lower clinical pregnancy and live birth rates

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The other retrospective analysis from 2009-2015 with over 3000 patients found that FR and LBR per cycle were higher in IVF than ICSI (67.1% vs. 62.3% p < 0.0001, 17.22% vs. 13.2% p < 0.001, respectively). They stated that "one less pregnancy in every 15 cycles where ICSI was used without an indication" [11]. One study specifically attempted to look at the use of ICSI in NMF to help reduce TFF and improve embryo quality [12].…”
Section: Unselected Patientmentioning
confidence: 99%
“…The other retrospective analysis from 2009-2015 with over 3000 patients found that FR and LBR per cycle were higher in IVF than ICSI (67.1% vs. 62.3% p < 0.0001, 17.22% vs. 13.2% p < 0.001, respectively). They stated that "one less pregnancy in every 15 cycles where ICSI was used without an indication" [11]. One study specifically attempted to look at the use of ICSI in NMF to help reduce TFF and improve embryo quality [12].…”
Section: Unselected Patientmentioning
confidence: 99%
“…However, even this hypothesis would be questionable according to the results of a similar recent retrospective study on a large group of women with mean age 37, and normo-spermic partners [29]. In that study, which had a design similar to ours, the fertilization rate, the number of frozen embryos, the cumulative pregnancy rate and the live birth rate were significantly lower for the couples treated with ICSI.…”
Section: Discussionmentioning
confidence: 62%
“…For preimplantation genetic testing (PGT) to be clinically applicable, intracytoplasmic sperm injection (ICSI) is usually required, rather than conventional in vitro fertilization (IVF) insemination method, owing to potential parental contamination from sperm and cumulus cells attached to the zona pellucida during conventional IVF (1)(2)(3)(4)(5)(6). However, in many available studies addressing non-male factor infertility, ICSI has not been proven to be beneficial for clinical outcomes, and the risk of chromosomal defects is increased in ICSI offspring (7)(8)(9)(10)(11)(12). Since sperm DNA fails to amplify under the conditions used for trophectoderm (TE) biopsy samples, and cumulus cells will be deliberately removed clearly in fresh IVF-PGT-A, the use of conventional IVF has been preliminarily explored in fresh genetic testing for aneuploidies (PGT-A) cycles in recent years (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%